2002
DOI: 10.1002/prot.10233
|View full text |Cite
|
Sign up to set email alerts
|

Docking of non‐nucleoside inhibitors: Neotripterifordin and its derivatives to HIV‐1 reverse transcriptase

Abstract: The docking of small molecules to proteins has played an important role in the understanding of drug/receptor interactions. An important drug/receptor interaction is between non-nucleoside inhibitors of HIV-1 RT and the non-nucleoside binding pocket. We report the results of docking calculations in which we have docked known and proposed non-nucleoside reverse transcriptase inhibitors to the type 1 virus. The proposed NNRTIs dock in a similar position and orientation as known inhibitors. In addition, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Hydrogen atoms and partial charges were added to the enzyme by MOE using the Kollman94 force field. MOE used the PEOE method to assign partial charges for the FAD cofactors and duroquinone (22)(23)(24). After all non-hydrogen atoms were fixed, the molecule was energy minimized by a combination minimization method comprised of steepest descent, conjugate gradient, and truncated Newton (25).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen atoms and partial charges were added to the enzyme by MOE using the Kollman94 force field. MOE used the PEOE method to assign partial charges for the FAD cofactors and duroquinone (22)(23)(24). After all non-hydrogen atoms were fixed, the molecule was energy minimized by a combination minimization method comprised of steepest descent, conjugate gradient, and truncated Newton (25).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental anti-HIV activity (pIC50) complied from references [10][11][12][13]. From the result of the QSAR study, it appears that the presence of halogen atom at X position with Balaben index will increase the HIV-1 binding affinity of TIBO derivatives.…”
Section: Utility Of Topological Parametermentioning
confidence: 99%
“…Experimental anti-HIV activity (pIC50) complied from references [10,11]. For the dataset of 16 analogues with well-defined activity, the HIV-1 non nucleoside reverse transcriptase inhibitory potency appears to be influenced by structural components.…”
Section: Utility Of Non-conventional Topological Parametermentioning
confidence: 99%
“…In docking studies, different search algorithms such as simulated annealing and genetic algorithm in combination with scoring function such as molecular mechanic calculations are used to study the binding of the candidate ligands to an enzyme with known structure. Docking studies involving NNI's and HIV-1 RT have been performed previously [28][29][30][31][32][33][34][35][36]. The results have shown that most inhibitors can docked into their crystal structure position.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, they are simple, non-expensive and expedite to design molecules with desirable biological activity [27]. Quantitative structureactivity relationship (QSAR) [16][17][18][19][20][21][22][23] and docking procedure [24][25][26][27][28][29] are two mostly used computational methods in drug design. In QSAR methodologies, a mathematical relationship, relating the biological activity to some molecular descriptors is obtained.…”
Section: Introductionmentioning
confidence: 99%